Togo : Joint Staff Advisory Note on the Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2008)
This Joint Staff Advisory Note (JSAN) reviews Togo's Interim-Poverty Reduction Strategy Paper (I-PRSP), which is aimed to strengthen political and economic governance, support economic recovery, and reduce poverty. The I-PRSP recognizes challenges to achieve the MDGs and the risks to its implementation and so paved the way for Poverty Reduction Growth Facility (PRGF) consideration. The JSAN urged the authorities to deepen the analysis on the links between growth policies and sectoral programs and expenditures and their impact on poverty reduction. Executive Directors also assessed the key PRSP implementation risks such as capacity constraints, political tensions, and adverse economic shocks.